Effects of Pelvic Floor Physiotherapy, with or without Weight Loss, on Urinary Incontinence in Obese Women: A non-Randomized Single Blind Clinical Trial - Seyedeh Saeideh Babazadeh_Zavieh; Behnoosh Vasaghi-Gharamaleki; Afsaneh Nikjooy; Seyed Mohammad Jafar Haeri; Javad Sarrafzadeh (Shiraz University of Medical Sciences, 2022)
Background: Obesity is known to be an important risk factor in the development of UI (urinary incontinence). Physiotherapy (exercise therapy and biofeedback) has been presented as a common treatment for the improvement of UI. Pelvic floor physiotherapy (PFPT) with weight loss (WL) may significantly improve UI in obese women. This study aimed to compare the effects of PFPT with and without WL on UI symptoms in obese women. Methods: This non-randomized clinical trial was performed with 51 middle-aged obese women with UI. Twenty-nine women in the PFPT group received 12 sessions of PFPT, and 22 women in the PFPT+WL group received 12 sessions of PFPT and nutritionist recommendations for WL. The outcome measures included anthropometric measurements, strength and endurance of pelvic floor muscles, intravaginal pressure (IVP), international consultation on incontinence questionnaire (ICIQ-SF), visual analog scale (VAS), and quality of life (QOL). All measurements were taken at baseline and after the 12-session treatment. Results: The PFPT+WL group had a 4.95 kg weight loss (p <0.001). Strength and endurance of PFM, IVP, ICIQ UI-SF, VAS, and QOL showed significant improvement in both groups (p <0.001). The ICIQ UI-SF and total I-QOL in the PFPT+WL group were significantly different from those in the PFPT group (p=0.015, p=0.033, respectively), (95% CI: 2.23 - 5.10 vs. 2.85- 5.35 and 180.48 - 214.67 vs. 164.13 - 203.39, respectively). Conclusion: The proposed protocol of applying PFPT with WL compared to PFPT alone led to more significant improvement in UI severity and QOL in middle-aged obese women with UI.